Optimalisasi Sektor Umkm Dalam Program Kampung Tematik Waru Brillian Di Desa Bojong Renged Kecamatan Teluk Naga Dalam Prespektif Smart Village - Tria Rama Nabila; Seno Santoso; Machrunnisa Machrunnisa (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study aims to determine the process, obstacles and efforts made in optimizing the MSME sector that runs in Waru Brillian Thematic Village in Bojong Renged Village, Teluknaga District. This research method uses qualitative methods. Data were collected by observation, interview and documentation techniques. The types and sources of data are primary data and secondary data. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The theoretical concept used in this study is the theoretical concept of a smart village according to Novi & Ella (2019) in (Herdiana, 2019) states that the dimensions used in a smart village are resources, technology, service chain, government, community and rural environment. . Based on the results of research on the MSME sector that runs in the Waru Brillian Thematic Village, seen from the success indicators of the smart village concept, it shows that the indicators for resources, service chains, government, community, and rural environment are in the good category or in accordance with the theory of success of the smart village. While the technology indicators are said to be not optimal so that there is a need to increase the use of technology, especially in the MSME sector in Waru Brillian Thematic Village. The inhibiting factors for the UMKM Waru Brillian Thematic Village include raw materials that are difficult to find because the plants in this thematic village do not vary yet, which hinders the production process, MSME food products also do not take care of licensing, for example, we do not have a halal certificate. the existence and limitations of the technology used by the people of Bojong Renged Village, Teluknaga District. Efforts to develop MSMEs that are running in Waru Brillian Thematic Village include the need for ongoing assistance to MSMEs, the need for digitalization of MSMEs and MSME actors must be more innovative in marketing MSME products.